Safe and favorable prognosis of thoracic endovascular aortic repair for the low-risk patients with non-acute type B aortic dissection - Nakamura, Ken; Kobayashi, Kimihiro; Nakai, Shingo; Sho, Ri; Arai, Shusuke; Ishizawa, Ai; Watanabe, Daisuke; Hirooka, Shuto; Ohba, Eiichi; Mizumoto, Masahiro; Kuroda, Yoshinori; Kim, Cholsu; et al. (Frontiers in Cardiovascular Medicine, 2024)
Objective: Preemptive thoracic endovascular aortic repair (TEVAR) has the potential to improve the prognosis of Stanford type B aortic dissection (TBAD), however it is important to determine whether it could be safely performed as a prophylactic treatment. This study aimed to determine the short-and long-term outcomes of preemptive TEVAR for uncomplicated TBAD with a small aortic aneurysm.We analyzed 212 patients with medically treated uncomplicated subacute TBAD between July 2004 and October 2019 in two Japanese academic centers. The short-and long-term prognosis of patients who underwent preemptive TEVAR and the changes in aortic diameter over time after TEVAR were analyzed. Aorta-related complications, aortic-related death and postoperative complications were recorded and analyzed. Analysis was performed on an intension-to-treat basis.Results: During follow-up, patients were divided into two groups: optimal medical treatment (OMT; n=185 [87%]) and preemptive TEVAR (n=27 [13%]).In all cases, aortic enlargement was the reason for therapeutic intervention in the preemptive TEVAR group. Propensity score matching yielded a cohort of 27 control patients with OMT (group A) and 27 patients who underwent preemptive 4 4 TEVAR (group B). Preoperative characteristics were similar between groups. In group B, only one patient developed type A dissection at a late stage and died from aortic rupture. Freedom from aortic-related death at 1/5/10 years was 100%/92%/92% in group B. Overall growth (mm/year) of max aorta was significantly smaller in the TEVAR group than in the control group (-3.7 ± 2.9 vs 0.4 ± 5.6, p<0.01), and the diameter of the false lumen was reduced (-8 ± 4.8 vs -1.3 ± 8.0, p<0.001).Conclusions: Short-and long-term outcomes of TEVAR for uncomplicated TBAD with a small aortic aneurysm were excellent, with few postoperative complications. After TEVAR, aortic remodeling was observed in the short term, suggesting that it may contribute to the prevention of aortic-related death due to rupture.